Obtenção e caracterização de biscoito tipo 'cookie' elaborado com farinhas de inhame (Colocasia esculenta L.) - Miamoto, Juliana de Brito Maia (2008)
The culture of the yam is of great cultural appeal, mainly in some areas of Brazil, however its use is low, because its consumption is restricted only to the cooked vegetable. Alimentary alternatives seeking to enlarge the yam consumption, that is a rich amilacea in several nutrients, mainly in functional nutrients, because to the yam is attributed to can healing and detoxification to hundreds of years. This work was accomplished with the objective of characterizing under physiochemical and nutritional aspects flours obtained from of the integral (mucilage and residue of the extraction of the mucilage) yam besides to increase biscuits these flours in the basic formulation of type cookie, that were capable to offer at least 25% of the human needs of alimentary fiber for adult individuals, besides functional nutrients as antocianina, polifenol, saponina, minerals and vitamins. The flours, obtained through lyophilization of the integral yam, mucilage and residue from the extraction of the mucilage, showed an income of 11,62% of integral yam, 19,69% of mucilage and 24,20% of residue of the extraction of the mucilage, being shown rich source of minerals potassium, zinc, manganese, phytochemicals (saponina, antocianina and polifenols) content and high tenor of alimentary fiber, what determined an increment from 40% of these flours to the basic formulation of biscuits type cookie. The constituintes (components) of centesimal composition, the nutrients present on the flours obtained from the yam, were transferred to the cookie. The cookies, mainly these elaborated with the flour of the residue demonstrated favorable physical characteristics as analternative to industrial production.